Evaluation of differential pulmonary perfusion using 99mTc macroaggregated albumin after the Fontan procedure. (11th December 2017) - Talwar, Sachin; Sankhyan, Lakshmi; Patel, Chetan; Sreenivas, Vishnubhatla; Choudhary, Shiv Kumar; Airan, Balram
Abstract: OBJECTIVES: The Fontan procedure [total cavopulmonary connection (TCPC)] is the final palliation for patients with univentricular physiology. We studied differential perfusion ratio and percentage uptake of a radiotracer in different zones of each lung following TCPC. METHODS: Between July 2015 and June 2017, 45 patients underwent 99m Tc macroaggregated albumin lung perfusion scan at a mean follow-up period of 49.3 ± SD 26.1 days following TCPC. Differential perfusion ratio and percentage uptake of the radiotracer in the upper, middle and lower zones of each lung were calculated. RESULTS: Post-foot injection [inferior vena cava (IVC) injection], preferential flow to the lungs was as follows: left lung ( n  = 13, 30.2%), right lung ( n  = 13, 30.2%) and uniformly to both lungs ( n = 17, 39.6%). Post-arm injection [superior vena cava (SVC) injection], preferential flow to the lungs was as follows: left lung ( n  = 13, 30.2%), right lung ( n  = 22, 51.2%) and uniformly to both lungs ( n = 8, 18.6%). The middle zone was perfused the most in both lungs. Total lower zone mean perfusion was higher than the upper zone following both SVC injection and IVC injection (34.1 ± SD 5.3% vs 17. ± SD 4.1% and 33 ± SD 5.0% vs 17.5 ± SD 4.1%, respectively). In patients with bilateral SVC, post-IVC injection, 6 (75%) patients had preferential flow to the right lung, whereas post-SVC injection, preferential flow to the left lung was visualized in 7 (87.5%) patients. CONCLUSIONS: Following TCPC, IVC blood was distributed uniformly in both lungs. SVC blood preferentially perfused the right lung. The middle zone was perfused the most in both lungs.